Self-determination of the transformation process of the body self-image in the structure of self-awareness of persons with cerebrospinal injuries - Bonkalo, Tatyana I. (2021)
The research objective is to determine the specific features of the influence of self-determination on the transformation of the body self-image in the self-awareness of people with cerebrospinal injuries. The study involved 2,482 people: 682 subjects (18 to 40 years old) with an injury sustained in a period of up to 2 years; 811 subjects (18-40 years old) with an injury sustained in a period of 2-5 years; 989 subjects (18-40 years old) with an injury sustained in a period of over 5 years. The study of the body self-image was carried out with the proprietary methodology of MSBSI (multidimensional study of the body self-image) and the BIQLI questionnaire by T.F. Cash. The dynamics of the body self-image in individuals within different post-injury periods has been determined. The strong correlations between the features of the body self-image and the development level of a person's self-determination have been revealed. Psychological recovery of persons with cerebrospinal injuries should include programs focused on the development of a person's ability of self-determination.